Culture and Green Advertising Preference: A Comparative and Critical Discursive Analysis - Liu, Shubo; Liu, Xiaoyuan (Frontiers in Psychology, 2020)
As environmental concerns began to emerge, companies started to target at the growing ‘green market’ and launch their green products. Companies’ green advertisings played an important role in facilitating corporate green marketing and fuelling the desire for environmental-friendly commodities. Applying a Critical Discursive Perspective, this study focuses on the corporate environmental advertisings in order to illuminate their discursive strategies and the process that corporate green advertisings generate and symbolically structure the necessity of green consumption. The comparing constructive characteristics and constructed meanings of green advertisings identified embody distinction in Western and Chinese cognitive style and process.